The Impact of Quality of Education and Higher Education on Economic Growth - Arman, Arman; Purwandaya, Budhi; Saefuddin, Asep (Universitas Negeri Semarang, 2020)
Education is the basic capital to create quality economic growth. Skillful and competitive human resources are a source of basic capital to create religious industrial technological innovation in order to support quality economic growth. This study aims to (1) analyze the relationship between education and growth in Indonesia and (2) compile a formulation of education policy as an important driving factor in long-term growth. The observation units analyzed were 33 provinces in Indonesia in the period 2013-2015. The data is then analyzed using the Data Analysis Panel approach. The results showed that the level of prosperity and prosperity was positively correlated with regional economic growth. This shows that the more qualified human development and increasing prosperity, the better economic growth in the region. Furthermore, the better the quality of education, the better economic growth. This result is inversely proportional to the large number of universities where the number of tertiary institutions does not have an influence on regional economic growth. This shows that the number of universities does not have a positive effect if it is not balanced with the number of qualified lecturers.